1994
DOI: 10.1007/bf00178201
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT3 receptor agonist 1-(m-chlorophenyl)-biguanide facilitates noradrenaline release by blockade of ?2-adrenoceptors in the mouse brain cortex

Abstract: We analyzed the facilitatory effect of the 5-HT3 receptor agonist 1-(m-chlorophenyl)-biguanide (mCPBG) on the electrically evoked noradrenaline release in superfused mouse brain tissue. In addition, we determined the affinities of mCPBG and two other 5-HT receptor ligands, namely 2-methyl-5-hydroxytryptamine (2-methyl-5-HT; also a 5-HT3 receptor agonist) and 5-carboxamidotryptamine (5-CT; a 5-HT1 receptor agonist) for alpha 2 binding sites. The latter two 5-HT receptor agonists were included because of the cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…We found the binding of each radioligand to be potently inhibited by selective ligands at their respective receptors and the results closely conform to previously published data (AM‐281 –Gifford et al. , 1997; rauwolscine –Schlicker et al. , 1994; imetit –Kathmann et al.…”
Section: Discussionsupporting
confidence: 91%
“…We found the binding of each radioligand to be potently inhibited by selective ligands at their respective receptors and the results closely conform to previously published data (AM‐281 –Gifford et al. , 1997; rauwolscine –Schlicker et al. , 1994; imetit –Kathmann et al.…”
Section: Discussionsupporting
confidence: 91%
“…We suggest that the lower concentrations of CPBG used here preferentially activates receptors other than the 5-HT 3 receptor, and so our results using CPBG should be interpreted cautiously. For example, although CPBG is a potent high anity 5-HT 3 receptor agonist (Kilpatrick et al, 1990), it has also been shown to interact with the catecholamines, facilitating the release of noradrenaline (Schlicker et al, 1994) and inhibiting the reuptake of dopamine (Campbell et al, 1995).…”
Section: Synaptic Facilitationmentioning
confidence: 99%
“…It is unlikely that the inhibitory action of 5-HT and SR 57227A in the mPFC could be indirectly mediated via activating GABAergic interneurons, as demonstrated in the hippocampus (Kawa, 1994;Piguet and Galvan, 1994;Ropert and Guy, 1991), since we have routinely included both GABA A and GABA B receptor antagonists, which completely blocked the inhibitory action of 0.5 mM GABA, in our recording medium. Alternatively, it is possible that 5-HT and SR 57227A could produce a potent inhibitory action on the NMDAinduced response by releasing DA in the mPFC, since it has been shown that 5-HT and 5-HT 3 receptor agonists increase the release of DA and other neurotransmitters in the brain (Blandina et al, 1989;Carboni et al, 1989;Chen et al, 1992;Consolo et al, 1994;Imperato and Angelucci, 1989;Jiang et al, 1990;Mongeau et al, 1994;Schlicker et al, 1994;Schmidt and Black, 1989). However, this is unlikely because the D2 agonist quinpirole exerted a limited depressant effect on NMDA-induced inward current in pyramidal cells of the mPFC, whereas the D1 agonist SKF 38393 enhanced this current (Zheng et al, 1996) and because the relatively selective D1 and D2 receptor antagonists failed to block 5-HT and 5-HT 3 agonists' depressant action on mPFC cells .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that 5-HT and 5-HT 3 receptor agonists increase the release of dopamine (DA) and other neurotransmitters in the brain (Blandina et al, 1989;Carboni et al, 1989;Chen et al, 1992;Consolo et al, 1994;Imperato and Angelucci, 1989;Jiang et al, 1990;Mongeau et al, 1994;Schlicker et al, 1994;Schmidt and Black, 1989). To ensure that 5-HT and SR 57227A did not cause the release of DA and other neurotransmitters and indirectly inhibit the NMDAevoked response in pyramidal cells of the mPFC, we performed experiments in Ca 2ϩ -free and low Ca 2ϩ (0.1 mM) plus Cd 2ϩ (0.2 mM) ACSF.…”
Section: Selectivity Of the Action Of Sr 57227amentioning
confidence: 99%